Performance of the 2019 EULAR/ACR systemic lupus erythematosus classification criteria in a cohort of patients with biopsy-confirmed lupus nephritis - Fei Han; Jianghua Chen; Lan Lan; Yanhong Ma; Huijing Wang; Yunjie Gao; Fanghao Cai; Xiaohan Huang; Pingping Ren; Yaomin Wang (Lupus Science and Medicine)
Objective To evaluate the performance of the European League Against Rheumatism/American College of Rheumatology (EULAR/ACR) SLE classification criteria in a cohort of patients with biopsy-confirmed lupus nephritis (LN) and their renal prognosis.Methods Patients with newly diagnosed SLE attending and followed up for >12 months were included. A retrospective review of all patients with renal biopsy fulfilling a consensus expert opinion during 2014 and 2018. Clinical, serological and pathological data were collected and each patient was assigned a high/low criteria scores (HS/LS) group. Survival curves for flare adjusted for multiplicity on renal flares, was applied to the two groups.Results Applying EULAR/ACR criteria in our cohort of 126 patients, 6 (4.76%) did not meet the criterion, resulting in a sensitivity of 95.24%. The EULAR/ACR criteria scores was positively correlated with SLE disease activity index scores. Additionally, we noticed that a significant difference in clinical and immunological manifestations between HS and LS group. We observed a higher proportions of class Ⅲ or Ⅳ LN and lower proportions of class Ⅱ or V LN (p=0.034) and pathological higher activity index in HS group (p=0.007). Compared with LS groups, patients involved more severe renal damage and achieved higher rate of complete remission in the HS group. The Kaplan-Meier exploratory analyses, adjusted for LN classification, estimated glomerular filtration rate, activity index and chronicity index and induction and maintenance treatments, showed that patients in the HS group had a tendency of higher renal flare risk than that in the LS group (HR=0.21, p=0.04).Conclusions The EULAR/ACR criteria performed high sensitivity in identifying SLE in this cohort of biopsy-confirmed LN. Patients with LN with high criteria scores had more extrarenal manifestations, and worse renal prognosis in the short and long terms.